Visualization analysis of research on Chinese cultural identity based on CiteSpace (2013–2022) - Niu, Chunyuan; Ng, Chwee Fang; Abdul Halim, Hazlina; Mustapha, Nik Farhan (Universiti Putra Malaysia, 2024)
Though extensively examined, research on Chinese cultural identity lacks systematic categorization, leading to uncertainties about evolving research priorities. This study addresses this gap by comprehensively analyzing Chinese Cultural Identity (CCI) development trends using the Web of Science database and CiteSpace, a scientific literature visualization and analysis tool in bibliometrics and scientometrics. This study examines Chinese cultural identity development from 2013 to 2022, encompassing research trends, global distribution of research institutions, and emergent hotspots. It uncovers a two-phase progression in Chinese cultural identity research: initial gradual exploration followed by rapid advancement. While research in this field is concentrated in China, the United States, Australia, the United Kingdom, Canada, Singapore, and Malaysia, it is noteworthy that research institutions are globally distributed. Three focal points (Chinese culture examination, cultural identity investigation, and cultural identity determinants) highlight the subject’s multifaceted nature. Additionally, emerging research frontiers include the empowerment of women in Chinese cultural identity, the role of information in shaping Chinese cultural identity, and the globalization of Chinese cultural identity, pushing the boundaries of understanding in this field. Further studies are encouraged to explore dissemination dynamics, adopt interdisciplinary approaches, and conduct in-depth case studies.